Perceptions of Transport Automation amongst Small- and Medium-Sized Road Haulage Companies in Finland - Markus Pöllänen; Heikki Liimatainen; Erika Kallionpää; Roni Utriainen; Hanne Tiikkaja; Timo Liljamo; Riku Viri; Steve O'Hern (Vehicles, 2022)
Transport automation is increasingly being studied from different perspectives; however, the perceptions of road haulage companies have received less attention. This study explores the views of representatives of small- and medium-sized road haulage companies on transport automation in Finland. We conducted an online survey to gather perceptions of automation, which received 254 responses from representatives of a range of different transport industries. The respondents’ views towards automation were generally negative. The overall view was that automation may not be possible for heavy vehicles in Finland due to the adverse weather and driving conditions. The perception was that road haulage automation is unlikely to occur before 2050 in Finland. The results provide valuable insight for vehicle manufacturers, technology developers, policy makers, and haulage companies. As the road haulage industry is dominated by small- and medium-sized companies, hauliers should be supported in actively implementing new technologies.